Kebaya in the nusantara archipelago / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2023)
Kebaya has been proposed to the United Nations Educational, Scientific and Cultural Organization (UNESCO) List of Intangible Cultural Heritage of Humanity for the year 2023 as a four-nation representation by Malaysia, Brunei, Singapore, and Thailand ("Malaysia in Joint Bid to Nominate Kebaya as Unesco Intangible Cultural Heritage", 2022). These four countries reached such an agreement since Southeast Asian nations all practice the tradition of wearing kebaya. Despite Indonesia's initial plan of nominating the kebaya as a single nomination, it has now been decided that Indonesia will join Singapore, Malaysia, Brunei Darussalam, and Thailand in the nomination submitted to UNESCO previously ("Indonesia Sertai Empat Negara Calonkan Kebaya di UNESCO", 2023).